Splitting and Motions of Dissipative Soliton Resonance Pulses in Mode-Locked Fiber Lasers - Lyu, Yanjia; Wei, Chen; Du, Wenxiong; Li, Heping; Liu, Yong (Frontiers in Physics, 2019)
We numerically investigated the splitting and motions of dissipative soliton resonance (DSR) pulses in an all-normal-dispersion Yb-doped fiber laser mode-locked by a non-linear optical loop mirror. At certain values of the system parameters, the initial single Gaussian pulse can evolve into an unstable DSR pulse with several dark solitons inside. After collisions of dark solitons, a big intensity dip occurs at the center of the DSR pulse, leading to the splitting of the DSR pulse. After splitting, the peak-to-peak separation between two DSR pulses increases at first and finally reaches a fixed value of 193 ps, indicating a steady-state multipulse operation The relative motions of separated DSR pulse originate from the phase shift.